Role of serum β2m in predicting severity of Coronary artery disease (University Heart Journal, 2020)
Background: Coronary artery disease is the principal cause of disability and mortality worldwide. Its prevalence is increasing around world. It is about 75% of deaths occurring in developing countries like Bangladesh. It is very important to know about the inflammatory risk factors of coronary artery disease for early assessment of coronary artery disease. Serumβ2-microglobulin (²2m) is a newly identified biomarker that has been found to increase in patients with coronary artery disease. Aims: To determine the role of â2m in predicting the severity of coronary artery disease.Methods: This cross-sectional study was carried out in Department of Cardiology and Laboratory Medicine, BSMMU, Shahbag, Dhaka during March 2017 to February 2018. Total seventy four patients who underwent coronary angiography as per criteria where included in this study. Serum β2-microglobulin (²2m)was done before angiography procedure by indirect ELISA method and severity of coronary artery disease was assessed by extent of diseased coronary vessels and SYNTAX score.Results: β2-microglobulin level was found higher (≥3/ml) in coronary artery disease patients which was statistically significant (p